Tingkat Penggunaan Smartphone pada Perkembangan Motorik Anak Usia 7- 10 Tahun di Kelurahan Beji Kecamatan Ungaran Timur Kabupaten Semarang (Indonesian Journal for Physical Education and Sport, 2022)
Now smartphones have become electronic goods that are easy to get, even children now easily use them to play. The purpose of this study was to find out whether smartphones are good or bad in the motor development of children aged 7-10 years in Beji Village, East Ungaran District, Semarang Regency. This study uses a descriptive quantitative approach. The method used in this research is survey research. The population of this study were all children aged 7-10 with a total of 148. In this study, 60 samples were taken using the purposive sampling technique aged 7-10 years using the Slovin formula. The results of the study using SPSS 23, the significant value of gross motor is 0.103> 0.05 and fine motor is 0.458> 0.05 and for motor is 0.112 it can be concluded that the value of sig> 0.05. The correlation results in this study are inversely proportional, children who are not dependent on smartphones on motor development, especially on fine motor development with a percent correlation value of 0.327. It was concluded that the level of smartphone use had no relationship with the motor development of children aged 7-10 years in Beji Village. suggestions for parents are expected to be more able to supervise or limit the use of smartphones in children and for children, it is expected to be able to limit the time of using smartphones and more activities outside the home, playing with peers or interacting with other people